Genomic Editing: The Evolution in Regulatory Management Accompanying Scientific Progress - Goberna, María Florencia; Whelan, Agustina Inés; Godoy, Perla; Lewi, Dalia Marcela (Frontiers in Bioengineering and Biotechnology, 2022)
Argentina currently counts with a regulation for genomic editing products whose criteria were updated as consultations were received to determine the regulatory status of these products. The aim of the regulation is to consider all organisms (animals, micro-organisms and plants) under the same NBT resolution independently and without being linked to GMO commercial regulations. In addition, it gives certainty to local working groups (teams of local developers and researchers), which can be seen in the number of developments and consultations carried out. The first results showed that the speed of innovation of these technologies was growing in a short period of time, giving more opportunity to local developers who showed interest in generating products in different species, crops and phenotypes.